Pregnancy management and successful delivery in a patient with Bland-White-Garland syndrome and a prosthetic mitral valve - M. O. Arslanbekova; D. Kh. Khizroeva; N. V. Samburova; E. S. Egorova (IRBIS LLC, 2018)
The article presents a clinical case of a pregnant woman with a prosthetic mitral valve and Bland-White-Garland syndrome. The proper pregnancy management resulted in a successful delivery of a full-term healthy child, thanks to the team approach of all specialists involved.